The Analysis of Transparency and Accountability in the Perspective of Good Governance in the Appointment of Village Officials in Kapuh Utara, Pesisir Selatan Regency - Soniati, Soniati; Syamsir, Syamsir (The Future of Education Journal, 2025)
This study aims to analyze the application of transparency and accountability principles in the process of appointing government officials in North Kapuh Village, Pesisir Selatan Regency, and to identify various obstacles in its implementation. The approach used is qualitative with descriptive methods. Informants were selected using a purposive sampling technique. Data were collected through field observations and interviews with informants, accompanied by documentation studies to support the research findings. Data validity testing was carried out using triangulation techniques. Data analysis includes data reduction, data presentation, and conclusion drawing stages. The results of the study indicate that the low application of transparency and accountability principles in the recruitment process of village officials in North Kapuh is caused by a weak supervisory system, lack of regulations, a closed bureaucratic culture, and minimal public awareness of the right to information and public oversight. Therefore, it is necessary to strengthen the supervisory function, increase the socialization of information transparency, and reform the village government governance to align with the principles of good governance.